Antonimi dalam Media Online CNN Arabic / Antonyms in CNN Arabic Online Media - Siti Zakiyatul Maghfiroh; Alifya Nur Wahyuni (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2023)
This study aims to describe the choice of words in the antonymy category found in the CNN Arabic online media. CNN Arabic itself is a news website based in Dubai, United Arab Emirates that provides ongoing Arabic-language international news regarding regional and international developments. Apart from that, world news, the Middle East, science and technology, entertainment, business and sports are also included on the CNN Arabic website. In presenting the news, there is a stylistics that has a construction of meaning relations. The stylistics contained in the news is the construction of meaning relations in terms of conflicting meanings or commonly referred to as antonyms. The research method used by researchers in this study is descriptive qualitative research, which is a research method that describes and analyzes in detail the data to be studied. The object to be studied is news in CNN Arabic. The results of this study indicate that there are 15 words that show conflicting meanings or antonyms in the CNN Arabic news.Abstrak: Penelitian ini bertujuan untuk menjabarkan pilihan kata dalam kategori antonimi yang terdapat pada media online CNN Arabic. CNN Arabic sendiri merupakan situs web berita yang berada di Dubai, Uni Emirat Arab yang menyediakan berita Internasional berbahasa Arab yang berkelanjutan perihal perkembangan regional maupun internasional. Selain itu berita dunia, Timur tengah, sains dan teknologi, hiburan, bisnis, dan olahraga, juga termuat dalam situs web CNN Arabic. Dalam menyuguhkan beritanya, terdapat sebuah stilistika yang memiliki konstruksi relasi makna. Adapun stilistika yang terdapat dalam berita tersebut adalah konstruksi relasi makna dalam hal pertentangan makna atau yang biasa disebut dengan antonimi. metode penelitian yang digunakan peneliti dalam penelitian ini adalah penelitian deskriptif kualitatif, yaitu sebuah metode penelitian yang mendeskripsikan dan menganalisis secara detail dari suatu data yang akan diteliti. Objek yang akan diteliti adalah berita dalam CNN Arabic. Hasil dari penelitian ini menunjukkan terdapat 15 kata yang menunjukkan pertentangan makna atau antonimi dalam berita CNN Arabic.